Activities of the sinus node pacemaking during the simulated atrial reentry. (16th December 2016) - Zhang, Hong; Li, Rui-juan; Huang, Xin; Yang, Zhao
Abstract: Numerous studies implicated the relationship between the sinus node dysfunction (SND) and atrial arrhythmias, but the pacemaker activities of sinoatrial node (SAN) during the atrial reentry before the formation of structural and electrophysiological remodeling in SAN were not well investigated. In the present study, a gradient two-dimensional model including SAN and atrium was built to reflect heterogeneities of the SAN. The reentrant wave was induced by the cross field method in the atrium. The simulation demonstrated a suppressed SAN spontaneous firing by the invading reentry and a 4:1 entrance block into the SAN at a reentrant cycle length of 80 ms. When the retrograde electrical excitation from atrium captured the SAN cell, the maximum diastolic potential of its action potential was found to become more negative with increased upstroke velocity. At the same time, the amplitudes of I f, I CaL and I Ks were enlarged. Besides, the interactions of the atrium and SAN presented a block of the sinus firing from exiting to the atrium while protecting the central SAN from the effects of the invading reentry. These findings suggested a link between SND and atrial reentry, and therefore were helpful in explaining the role of atrial arrhythmias in SND.